Experimental evidence for sulphide magma percolation and evolution : relevant to the chromite bearing reefs of the Bushveld Complex - Koegelenberg, Corne (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc)--Stellenbosch University, 2012.